Universe Unveiled: The Cosmos in My Bubble Bath - Vishveshwara, C. V (Springer, 2016)
The bubbles were swirling all around me, massaging my body. As I luxuriated in this fantastic bath, I gasped realizing that those bubbles carried with them miniature galaxies bringing the entire Cosmos into my bathtub...